2020
DOI: 10.14710/jitaa.45.1.15-27
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bali cattle based on birth weight and calving interval records at West Nusa Tenggara Province of Indonesia

Abstract: Birth weight and calving interval are included of productivity traits that can be increased by selection program. However, the standard of desirable birth weight in cattle during the selection program is important to prevent dystocia incident risk. This study was aimed to select Bali cattle (Bos javanicus) based on Estimated Breeding Value of birth weight (EBVBW) and Most Probable Producing Ability of birth weight (MPPABW) and calving interval (MPPACI). Total of 758 records data of BW were collected from Lombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In this study, the average CI of Bali cow ranged from 364.7 days to 406.3 days. This result is similar to the average CI of Bali cow in several regions in Indonesia, which ranges from 360.9 days to 457.8 days (Gunawan et al 2011;Pemayun et al 2014;Said et al 2020;Sari et al 2020). The results showed that BCS and different rearing systems do not significantly affect CI of Bali cow.…”
Section: Calving Intervalsupporting
confidence: 83%
“…In this study, the average CI of Bali cow ranged from 364.7 days to 406.3 days. This result is similar to the average CI of Bali cow in several regions in Indonesia, which ranges from 360.9 days to 457.8 days (Gunawan et al 2011;Pemayun et al 2014;Said et al 2020;Sari et al 2020). The results showed that BCS and different rearing systems do not significantly affect CI of Bali cow.…”
Section: Calving Intervalsupporting
confidence: 83%
“…In addition to reproductive problems, many other factors also cause low performance, including feeding problems, inbreeding and disease management. The desired birth weight standard in the selection program is important to prevent the occurrence of dystocia (Said et al, 2020).…”
Section: Body Weight Of Female Balinese Cattle In East Halmahera Regencymentioning
confidence: 99%